Crosstalk between the circadian clock, intestinal stem cell niche, and epithelial cell fate decision - Ji Liu; Zhihui Jiang; Juanmin Zha; Qiong Lin; Weiqi He (Genes and Diseases)
The circadian rhythm, a 24-h cycle, plays a crucial role in regulating gut physiological processes, particularly the proliferation and differentiation of intestinal epithelial cells, which are essential for gut homeostasis and repair. This review discusses the complex interactions between circadian rhythms, cell cycle regulation, and key signaling pathways (Wnt, Notch, and Hippo) in the context of the intestinal stem cell niche and epithelial cell fate decisions. Key molecules such as brain and muscle ARNT-like 1 (BMAL1), circadian locomotor output cycles kaput (CLOCK), hairy and enhancer of split 1 (Hes1), and Yes-associated protein/transcriptional coactivator with PDZ-binding motif (YAP/TAZ) coordinate stem cell functions with circadian rhythms. We discuss how Notch signaling regulates the cell cycle and interacts with circadian rhythms. Additionally, we explore the role of Hippo-Wnt signaling in balancing cell proliferation and differentiation. Furthermore, we highlight the intricate relationships between circadian clock components and signaling pathways, emphasizing the importance of temporal coordination in determining epithelial cell fate. We also discuss shared enzymes, including casein kinase 1 delta (CK1δ), glycogen synthase kinase 3 (GSK3), and AMP-activated protein kinase (AMPK), which play a role in regulating the cell cycle, circadian rhythm, and signaling pathways. In summary, this review offers valuable insights into the regulatory mechanisms that control stem cell behavior and epithelial cell differentiation, suggesting promising directions for future research in intestinal biology and tissue homeostasis.